Service Learning to Increase Utilization of X Video Editing Software Features within Limited Facilities for the Youth of Gereja Kristen Pasundan Cideres - Pin Panji Yapinus; Leon Karsten; Emmanuel F. Sigit Bayu P.; Gilberth Giandy Taruna Kesumah; Rudianov Z.A. Parera; Richard Anderson (Journal of Innovation and Community Engagement, 2021)
The service learning in multimedia skills for teenagers and young people as training program for the community was conducted through the expertise of Bachelor Program in Computer Engineering, Faculty of Engineering, Universitas Kristen Maranatha, for Gereja Kristen Pasundan (GKP) Cideres. The purpose of this training was to equip people with skills or knowledge that can be useful in daily activities. As this training was given during the Covid-19 pandemic, by requirement of health and safety protocols, the service learning was implemented online via the internet in a form of webinar. Online digital activities are increasingly important as conventional physical interactions and communication in work or study environment become unsafe and to be avoided or to be done less often than usual. Unfortunately for most people, technical skills for working or studying online are not yet adequate, especially in multimedia using some recent tools and softwares. So in this program, basic multimedia producing skills using Microsoft Photos (video editing feature) and Microsoft Power Point were introduced. The end result of the training was satisfactory, as those who participate are being able to produce simple digital multimedia presentation using the aforementioned tools and softwares. The training program was held online on November 28th, 2020 via Zoom Meeting Application, and was made possible thanks to the collaboration of Bachelor Program in Computer Engineering with the Directorate of Student and Alumni Affairs, Universitas Kristen Maranatha. Keywords: Covid-19 pandemic; multimedia; service learning